100 Years of Adolescence and its Prehistory From Cave to Computer. Issue 1 (31st March 2017) - Stambler, Morris J. L.
ABSTRACT: In an attempt to understand the impact of our transition into the digital era, this paper looks at adolescence across the sweep of human history, reviewing psychoanalytic conceptions of adolescent development with a particular focus on the end of adolescence. Turning to paleobiology, adolescence and early childhood are phases unique to modern humans, allowing the accumulation of knowledge and culture and a form of cognition, autonoesis. As human society becomes increasingly complex, the length of time before achieving adulthood has increased. The digital revolution has brought new stresses and strains extending this even further. Arnett has proposed that another phase, emerging adulthood, be introduced between adolescence and early adulthood. This concept and dynamic systems theory are both reviewed. This paper suggests that notions of psychic structure are in need of revision as they are overly linear and based on antiquated scientific metaphor. These developments have implications for clinical practice with adolescents, emerging adults, and their parents, and might require adjustments to new ways of engaging with the broader issues of mental health.